If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 = -6q Solving 48 = -6q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '6q' to each side of the equation. 48 + 6q = -6q + 6q Combine like terms: -6q + 6q = 0 48 + 6q = 0 Add '-48' to each side of the equation. 48 + -48 + 6q = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 6q = 0 + -48 6q = 0 + -48 Combine like terms: 0 + -48 = -48 6q = -48 Divide each side by '6'. q = -8 Simplifying q = -8
| 8x+12=96 | | 8x+y=96 | | 5x+3+7x+5=15x-18 | | 8x+x=96 | | -21u+84=-15u-20 | | -6(4x-6)=-24x+36 | | 3.6n=1.6n+24 | | -6x-10=-5x | | 3x+15+42=168 | | 2236000-17740x=-45 | | aw+ay=z | | -14x-2(x+4)=5-(x+2) | | xy+xw=z | | 3x*y*y*3*x*x= | | 3x+12+21=207 | | -243=-9(10)+x | | wx+xy=z | | 6x-6y+2z=-5 | | 5m=-0.7 | | Xsquared-9x=22 | | 2236000-17740x=15 | | x^2-6x=18+0 | | -14-2(x+4)=5-(x+2) | | -2(x)=-7 | | -9-7=8n-6(2+n) | | -3x+12+4x=5+x+7 | | -4x=9-2y | | F(-2)=-7 | | 5(n+2)=3(5+10n) | | 9.6=16y | | 5x^2+3x+0=0 | | 0.70x+0.60(70)=0.35(94) |